Learning styles applied to virtual foreign language classrooms - Macías Romero, Wilmar Darío (Rastros Rostros, 2015)
Introduction: the objective of this paper is to propose a virtual classroom model for foreign language teaching aimed at first semester students at a private university in Bucaramanga, Colombia. Methodology: such classroom is sought to respond to the institution’s teaching philosophy and the methodological communicative proposal inherent in teaching English as a foreign language, which is in turn in accordance with students’ learning styles. Results: 55 learners of the first English level took the Felder and Silverman test to identify dominant learning styles, thus determining that most of them are visual, active, sensory and sequential learners. Then, the tools available in the moodleplatform and how each of them could meet the needs of learners in a timely manner were identified. Conclusions: finally, a virtual classroom model was proposed using the resources available on the platform, according to students’ learning styles